Consumer profile of Coalho Cheese in the State of Paraíba (Research, Society and Development, 2019)
Coalho's cheese is a typical product that is part of the culture and traditions of the Northeast region of Brazil, being consumed in natura or as an ingredient in several dishes typical of the region. The objective of this research was to characterize the consumer profile of Coalho cheese in the state of Paraíba. The study was characterized by the use of a questionnaire containing 18 questions, in the interview format, of a total sample of 400 interviewees in the cities of João Pessoa, Campina Grande, Santa Rita and Patos. The predominant age group was older than 45 years, most of them attended high school and all the interviewees consumed milk or milk products. Cheese is the most consumed milk product, followed by milk and yogurt. Respondents like to consume more of the roasted, natural and fried Coalho cheese. Most do not observe the validity of the cheese, however, be careful about hygiene at the time of purchase. Therefore, it was observed that the consumers of rennet cheese from the cities evaluated are male, with secondary school and age over 45 years, mostly consumed Rennet cheese once a week, at breakfast, mainly roasted.